Kemampuan Petugas Menggunakan Pedoman Evaluasi Pengelolaan Dan Pembiayaan Obat - Azis, Sriana; Hherman, M; Mun'im, Abdul (Majalah Ilmu Kefarmasian, 2005)
One important aspect of district public health service is the management and budgeting of drugs. Up to this time no indicators can be used yet as guidelines for evaluating drug management and budgeting effectiveness in a district in Indonesia. The objective of this study is to determine the effect of training managing drug staff on the evaluation capability increase and their knowledge. Training has been conducted twice in 2 provinces, 4 districts ex HP IV each, covering Dinas Kesehatan, GFK, 5 PHCs per district and 300 outpatients. There are 7 groups of indicator which include a total of 29 indicators. Training involved computation of indicators of drug management and budgeting in a district. Tests were carried out before training and after the first and second training. Data were analyzed using paired t-test for the effect of training on the increase of knowledge and capability of managing drug staff in indicator computation for the evaluation of drug management and budgeting as well as linear regression for the relation between education and working experience of the staff and unpaired t-test for the difference in the increase in knowledge of pharmacy assistant and non pharmacy assistant. Results from the study on 54 managing drug staff in 8 district shows that knowledge increase significantly after the first and second training, whilst the latter increase is greater than the former one and that the increase in knowledge of pharmacy assistant exceeds that of non pharmacy assistant.